Confounding effect of blood volume and body mass index on blood neurofilament light chain levels. Issue 1 (1st January 2020) - Manouchehrinia, Ali; Piehl, Fredrik; Hillert, Jan; Kuhle, Jens; Alfredsson, Lars; Olsson, Tomas; Kockum, Ingrid
Abstract: Blood Neurofilament light chain (NfL) has been suggested as a promising biomarker in several neurological conditions. Since blood NfL is the consequence of leaked NfL from the cerebrospinal fluid, differences in individuals' Body Mass Index (BMI) or blood volume (BV) might affect its correlation to other biomarkers and disease outcomes. Here, we investigated the correlation between plasma NfL, BMI, and BV in 662 controls and 2, 586 multiple sclerosis cases. We found a significant negative correlation between plasma NfL, BMI/BV in both groups. Our results highlight the potential confounding effect of BMI/BV on associations between blood NfL and disease outcomes.